MEMBANGUN MASA DEPAN: PENDAMPINGAN MASYARAKAT MELALUI PENGABDIAN DAN EDUKASI ISLAM DI KECAMATAN SUKODONO SIDOARJO - Badriyah, Laila; Hidayati, Nurul (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
Student service through the Real Work Lecture Program (KKN) plays an important role in empowering the community, especially in the field of education. This study focuses on describing the stages and effects of the mentoring program carried out by KKN students, which aims to improve the quality of education in Wilayut Village, Sidoarjo. This assistance prioritizes several main areas: counseling activities, training, tutoring, and community social activities. We use the Participant Action Reseach (PAR) by involving students, teaching staff, parents, and community leaders. Research findings show that efforts to assist KKN students successfully increase student learning enthusiasm, introduce a new teaching approach to teachers, as well as raising awareness and active involvement of parents in supporting children's learning activities at home. Furthermore, this empowerment initiative encourages the formation of independent learning groups and optimizing local resources for educational purposes. Therefore, this program recommends a sustainable collaboration between higher education institutions, the village government, and the community in order to maintain the progress of the education that has been achieved after the Community Service Program ends.